Fiscal Adjustments and the Probability of Sovereign Default - Christoph A. Schaltegger; Martin Weder (Center for Research in Economics, Management and the Arts (CREMA), 2013)
Based on probit estimates, this paper analyzes the effects of fiscal consolidation on the prob- ability of sovereign defaults in the short run. Using a panel of 104 developing countries from 1980 to 2009 and controlling for various economic, fiscal and political fa ctors, we find that fiscal adjustments in general do not significantly reduce the probability of default even if they are large. Instead, the composition of budget consolidation is decisive in reducing default risk. In contrast to industrialized countries, expenditure based adjustments are not successful while revenue based adjustments lower the probability of default in the following year by 33 to 56 percent. This finding also holds when economic growth is low or government debt is high as well as when IMF lending is taken into account.
Keywords: E62; H62; H63; 330; sovereign default; fiscal policy; fiscal adjustment; bailout